Flipbook Platform E-Module Development: Geographic Information Systems Subject - Sakinatun Najmi Sibarani; Harun Sitompul; Keysar Panjaitan (Randwick International of Education and Linguistics Science Journal, 2024)
This research aims to determine the feasibility and effectiveness of e-modules with the Flipbook platform in the Geographic Information Systems (GIS) Class XI Geospatial Engineering subject at SMK Negeri 1 Percut Sei Tuan. This research applies the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Develop, Implement, and Evaluate). The research subjects were 30 students of Class XI Geospatial Engineering at SMK Negeri 1 Percut Sei Tuan. This research involved validation tests by material experts, media experts, and learning design experts, as well as trial stages, namely individual trials on 3 students, small group trials on 6 students, and limited field trials on 30 students. The research results show that the E-Module with the Flipbook platform is suitable for use based on media expert validation of 89.17% (very feasible), material expert validation of 92.13% (very feasible), and learning design expert validation of 88.71% (very feasible). In the individual trial, the score was 91.47% (very decent), the small group trial got a score of 92.33% (very decent), and the field trial got a score of 96.14% (very decent). The use of E-Modules with the Flipbook platform in GIS subjects is more effective than conventional whiteboard media, as can be seen from the results of tcount = 1.91 and tTable = 1.672, where 1.91 > 1.672 at the significance level α = 0.05. This shows that H0 is is rejected, and the alternative hypothesis (Ha) is accepted. This means that there is a noticeable difference in student learning results between the experimental and control classes with a significance level of 5%. The effectiveness value of the E-Module with the Flipbook platform is higher, namely 84.7%, compared to student learning outcomes using whiteboard media of 80.8%.